2018
DOI: 10.1021/acs.cgd.7b01768
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Chemical Bonding Dependence of Mechanical Properties in a Family of Metal-Formate Coordination Polymers

Abstract: Mechanical properties of a family of three-dimensional ammonium metal-formate coordination polymers ([AmineH n ]­[M­(HCOO)3] n , n = 1–4), in relation to their organic amine cation sizes, framework topologies, hydrogen bonding modes, and metal cation radii have been systematically studied via single crystal nanoindentation experiments. Our findings demonstrate that the moduli and hardnesses of these formate frameworks are primarily dominated by their solvent accessible volumes (SAVs), where formates with high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…Up to now, the electronic and elastic properties of inorganic and organic-inorganic perovskite materials have been comprehensively researched. [17][18][19][20][21][22] However, very limited information is known about the electronic structures and elastic properties of metal-free perovskite materials, 23,24 which will certainly delay their future industrialization. In this work, the electronic and elastic properties of a family of metal-free perovskites: [(C 4 N 2 H 12 )(NH 4 X 3 )ÁH 2 O] (X = Br, Cl, I), called PIP-Cl, PIP-Br and PIP-I, respectively, have been systematically investigated, using the first principle calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the electronic and elastic properties of inorganic and organic-inorganic perovskite materials have been comprehensively researched. [17][18][19][20][21][22] However, very limited information is known about the electronic structures and elastic properties of metal-free perovskite materials, 23,24 which will certainly delay their future industrialization. In this work, the electronic and elastic properties of a family of metal-free perovskites: [(C 4 N 2 H 12 )(NH 4 X 3 )ÁH 2 O] (X = Br, Cl, I), called PIP-Cl, PIP-Br and PIP-I, respectively, have been systematically investigated, using the first principle calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal of the RuZn polymer also shows the adjacent chains have a moderate level of hydrogen bonding (Figure S11) between them, with a distance of 3.29 Å between the two formate groups bonded to the zinc cation. Effective hydrogen bonding through formate groups has been shown in previous MOFs and coordination polymers [37,38] . The hydrogen bonding, coupled with the π–π interactions between the overlapping dqp ligands of adjacent chains leads to improved stability in the RuZn polymer.…”
Section: Resultsmentioning
confidence: 89%
“…polymers. [37,38] The hydrogen bonding, coupled with the π-π interactions between the overlapping dqp ligands of adjacent chains leads to improved stability in the RuZn polymer. Powder X-ray diffraction (PXRD) of the polymer was compared with the simulated XRD from the single crystal (Figure S12).…”
Section: Chemphotochemmentioning
confidence: 99%
“…This finding agrees with previous work on the effects of B-X bonding on the mechanical properties of hybrid and molecular perovskites. It has been shown that stiffer B-X bonds achieved through greater ligand-field stabilisation 18,33 or through greater electronegativity differences properties 11,34,35 result in stiffer materials. The direct effect of B-X bonding on the bulk modulus suggests that it would be interesting to investigate how crystal chemistry can be used to alter the mechanical properties across a range of different chemical environments.…”
Section: Resultsmentioning
confidence: 99%